Explaining the emergence of norms - Kuniński, Miłowit (Journal of Public Governance, 2013)
Since the second half of the 20th century, the game theory, and particularly the Prisoner’s Dilemma, has been widely used to explain the emergence of norms (Buchanan, Gauthier, Harsanyi, Nozick, Rawls, Ullmann-Margalit). Nevertheless, in light of deeper analyses, it has been demonstrated that the Prisoner’s Dilemma is not enough, since its matrix itself is determined by norms which could not be explained in its own terms (Ullmann-Margalit, de Jasay). Following E. Ullmann-Margalit, the author argues that the explanation of norms involves three normative levels: norms of rational decision making, solidified in the process of group selection; moral norms based on the action patterns determined by the rational decision making of the Prisoner’s Dilemma structure; and finally norms designed and selected in the process of group selection and critical assessment of their meaning and consequences.